1991
DOI: 10.1172/jci115138
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory burst oxidase and three of four oxidase-related polypeptides are associated with the cytoskeleton of human neutrophils.

Abstract: Resting and phorbol-activated human neutrophils were separated by treatment with Triton X-100 into detergent-extractable and cytoskeleton fractions. Respiratory burst oxidase activity was restricted entirely to the cytoskeleton. The cytoskeleton also contained 15% of the neutrophil cytochrome b5!, an oxidase-associated heme protein, as well as most of the oxidase-related cytosolic polypeptide p67x. In contrast, the components of the oxidase-associated phosphoprotein family p47'" were found almost exclusively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(81 citation statements)
references
References 33 publications
3
77
0
1
Order By: Relevance
“…It has been shown that actin can directly interact with components of the oxidase. For example p47 phox , p21rac and p67 phox have been localized in the detergent-insoluble cytoskeletal fraction of stimulated neutrophils (Knaus et al, 1992;Nauseef et al, 1991;Wientjes et al, 2001;Woodman et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that actin can directly interact with components of the oxidase. For example p47 phox , p21rac and p67 phox have been localized in the detergent-insoluble cytoskeletal fraction of stimulated neutrophils (Knaus et al, 1992;Nauseef et al, 1991;Wientjes et al, 2001;Woodman et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Separate rabbit polyclonal antibodies against recombinant p47 phox (R360) and p67 phox (R1469), p22 phox holoprotein (R3179), and a 12-amino acid C-terminal fragment of gp91 phox (R2085) were kindly provided by Dr. M. T. Quinn (Montana State University) (22,23). Anti-p47 phox and anti-p67 phox monoclonal antibodies were purchased from Transduction Laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…Fractions-Extracting cell protein into Triton X-100-soluble and -insoluble (cytoskeleton) fractions was performed as described previously (23,30) with some modifications. Confluent PIEC were washed twice in ice-cold PBS and detached by scratching.…”
Section: Separation Of Whole Cell Protein Into Triton X-100-soluble Amentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide generation is confined to the phagocytic vacuole when a particle is engulfed by the phagocyte, a localization that could be affected by the reorganization of the cytoskeleton that accompanies formation of the vacuole. At least a proportion of p67 phox , but very little p47 phox , remains associated with the detergent-insoluble material after the addition of Triton X-100 to neutrophils, suggesting a possible cytoskeletal attachment (Nauseef et al, 1991;Woodman et al, 1991). In addition, activation of the respiratory burst by a chemotactic peptide or by phorbol myristate acetate (PMA) is associated with changes in the shape of the neutrophils (Wymann et al, 1989), also probably a reflection of cytoskeletal involvement (Keller et al, 1995).…”
mentioning
confidence: 99%